Effect of the electric-field distribution on the morphology of dot-array gratings fabricated by AFM-based nanolithography. (2017) - Hu, Kexiang; Long, Fei; Wang, Qingkang
Local electric-field-induced anodic oxidation is one of the earliest and most extensively studied techniques in bias-assisted AFM nanolithography. The electric field provides the oxidation kinetics of nanoscale electrochemical reaction and controls the spacial resolution of the fabricated structures. Once electric field is formed, its distribution and intensity can be modified by changing the tip-sample voltage and separation. In this paper, the influence of the bias voltage on the three-dimensional (3D) radial electric field intensity distribution in the space between the tip and the sample, the influence of the electric field strength on dot-array grating structures and the morphology distribution of the nanodot structure in the dot-array grating have been analysed deeply.